Laparoscopic Retrieval of a Peritoneal Mouse - Dara O. Kavanagh; Diarmaid Moran; Robert Flynn; Paul C. Neary (Case Reports in Medicine)
A 67-year-old Caucasian male was referred by the urology service with a history of incomplete bowel emptying. He complained of tenesmus. MRI scan suggested a leiomyoma lying anterior to the rectum. He underwent examination under anaesthesia and attempted endorectal ultrasound and biopsy. However, the lesion seemed to migrate cranially and was impalpable. At laparoscopy, a mobile, unattached, 5.5×5×3.5, cream-coloured ‘egg was retrieved from the retrovesical space. Histology confirmed a hyalinised fibrocollagenous lesion lined with mesothelium. A comprehensive review of the literature is presented.